2018
DOI: 10.1016/j.nbd.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nicotine improves cognitive and social impairment in mice overexpressing wild type α-synuclein

Abstract: In addition to dopaminergic and motor deficits, patients with Parkinson's disease (PD) suffer from non-motor symptoms, including early cognitive and social impairment, that do not respond well to dopaminergic therapy. Cholinergic deficits may contribute to these problems, but cholinesterase inhibitors have limited efficacy. Mice over-expressing α-synuclein, a protein critically associated with PD, show deficits in cognitive and social interaction tests, as well as a decrease in cortical acetylcholine. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 102 publications
2
20
0
Order By: Relevance
“…Levodopa or D1 agonism, but not D2 agonism rescues the deficits in novel object recognition and hippocampal LTP (Bonito-Oliva et al, 2014b ; Loiodice et al, 2018 ) suggesting that early dysfunction not only occurs in dSPN circuits but are manifesting in D1-dependent systems that extend beyond the striatum. Similar cognitive deficits have also been observed in alpha-synuclein overexpression (Subramaniam et al, 2018 ). MitoPark mice have progressive degeneration of DA neurons (Ekstrand et al, 2007 ) with motor impairment beginning at 12 weeks of age (Galter et al, 2010 ).…”
Section: Spn Dynamics Preceding Motor Dysfunctionsupporting
confidence: 69%
“…Levodopa or D1 agonism, but not D2 agonism rescues the deficits in novel object recognition and hippocampal LTP (Bonito-Oliva et al, 2014b ; Loiodice et al, 2018 ) suggesting that early dysfunction not only occurs in dSPN circuits but are manifesting in D1-dependent systems that extend beyond the striatum. Similar cognitive deficits have also been observed in alpha-synuclein overexpression (Subramaniam et al, 2018 ). MitoPark mice have progressive degeneration of DA neurons (Ekstrand et al, 2007 ) with motor impairment beginning at 12 weeks of age (Galter et al, 2010 ).…”
Section: Spn Dynamics Preceding Motor Dysfunctionsupporting
confidence: 69%
“…Recently, Federica Bono et al ( 2019 ) showed that nicotine activated the dopamine D3R-nAChR complex and prevented αSyn accumulation in primary cultures of mouse dopaminergic neurons and human iPSC-derived dopaminergic neurons. However, chronic nicotine administration showed no effect on the levels of αSyn in the SNpc and striatum of Thy1-αSyn mice (Subramaniam et al, 2018 ). Besides, nicotine has intracellular machinery that governs protein folding, transport and turnover via regulating endoplasmic reticulum and mitochondrial health (Srinivasan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…SNCG expression is normally restricted to the brain and peripheral neuronal tissues [ 14 ], and its aberrant expression in tissues other than those of the neuronal system is highly associated with human malignancy. Previous studies have reported that nicotine acting on brain nAChRs may affect SNCA aggregation, resulting in neuroprotection [ 15 17 ]. Recently, we reported that SNCG is abnormally expressed in OSCC and that its expression is strongly correlated with disease progression [ 2 ].…”
Section: Introductionmentioning
confidence: 99%